Atomistic study of coreshell and functionally graded nanospheres under compressive loading. (15th July 2022) - Malakar, Prottay; Anan, Md Al Rifat; Islam, Mahmudul; Thakur, Md Shajedul Hoque; Mojumder, Satyajit
Abstract: Functionally grading and coreshell are two interesting engineering modifications to nanomaterials structure for tailored applications in electronics, energy conversion devices and so on. Understanding the mechanical response of these nanostructures are of particular importance to ensure the reliability of these devices under service conditions. In this paper, functionally graded and coreshell Silver–Gold (Ag–Au) nanospheres are studied under compression load using molecular dynamics simulation. The fracture and deformation mechanism along with the incipient plasticity through dislocation nucleation and propagation has been studied for both functionally graded and coreshell structure for different percentages of Ag and Au of the nanosphere. Our results indicate that plastic deformation is dictated by the partial dislocation nucleation and propagation from the contact surface which varies as the alloying percentages of the coreshell and functionally graded nanosphere. An inverse size effect is observed for the mechanical properties which also affects the deformation mechanism of the nanosphere by forming stacking fault tetrahedra for both the nanostructures. For a range of Ag percentages in Au, the coreshell nanospheres showed higher compressive strength compared to functionally graded nanospheres. As coreshell and functionally grading are two promising nanoscale materials design, current work will inspire developing new metal nanospheres to harness the materials potential for different engineering applications. Graphical abstract: Highlights: Coreshell and functionally graded nanospheres are investigated using MD simulations. Nanoscale materials design is performed varying alloying percentages in coreshell and FGM nanostructures. Mechanical response and deformation mechanism shows significant dependence on the nanostructures. Coreshell nanostructures outperforms the FGM nanostructure in mechanical response. Inverse size effect is observed for both nanostructure.